Where are all the bodies?—Defensive representational strategies in a time of cataclysmic change. (28th June 2019) - Moss, Donald
Abstract: In this essay, the author addresses the enormous challenge of coming to terms with our mental representations of the impending catastrophe associated with climate change. From the morality tale of the Biblical Flood, in which those who sinned by overindulging their instinctual pleasure were destroyed by water, to the current global crisis in which the excesses of unchecked industrialization and greed threaten the world "again, " the "slow violence" we are living through is sparsely represented in the analytic situation. The overwhelming nature of the changes we are witnessing, from pollution, mass extinction, and shrinking land mass, to massive social upheaval, victimizes us all.